Hubungan Antara Modal Manusia (Human Capital) dan Modal Finansial (Financial Capital) dengan Partisipasi Anggota Lembaga Masyarakat Desa Hutan (LMDH) dalam Program Pengelolaan Hutan bersama Masyarakat (PHBM) - Nor Firman, Rachmad; Sholikha, Aqidatus (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2020)
This research is an explanatory research, while the method used is a survey method in Tlekung Village, Junrejo District, Batu City. In this study, 24 samples were determined based on simple random sampling. Data analysis used descriptive analysis and Rank Spearman correlation analysis. The results in this study are as follows: 1) The human capital condition of LMDH members is in the high category and the financial capital of LMDH members is in the medium category. 2) LMDH members' participation in this PHBM program is in the high category. 3) There is a positive relationship between human capital and the participation of LMDH members in the Community Forest Management Program (PHBM), and there is no relationship between financial capital and the participation of LMDH members in the PHBM program. Further research is needed regarding the participation of LMDH members on forest management in the PHBM Program with the condition of human capital, for example regarding different levels of education and financial capital or on the factors that influence them, so that better government policies can be formulated in the forestry sector, especially related to Community Forest Management (PHBM) program.